RISK CHARACTERIZATION AND CLASSIFICATION IN HYPERTENSIVE URGENCY AND EMERGENCY EVENTS - Petrônio Barros Ribeiro de Jesus; Maria Helena Baena de Moraes Lopes; Ian Cesar Cardoso Toti; Vinícius Freitas Pinto Silva; Maria Inês Monteiro; José Luiz Tatagiba Lamas (Universidade Federal do Paraná, 2016)
The aim of this study was to characterize patients with hypertensive urgency or emergency events in an emergency care unit in the state of Minas Gerais, regarding their socioeconomic conditions, blood pressure levels, and risk classification. This is a cross-sectional and retrospective study based on secondary data of 63 records of patients treated from October to December of 2013. Data were collected in 2014 by means of a form containing the patient's data and risk classification. The chi-squared test and a 5% significance level was used for data analysis. The most prevalent age groups were 41-45 (15.9%) and 46-50 years (19%).The systolic and diastolic blood pressure averaged on levels 170-219 mmHg and 120-129 mmHg, respectively. Although the presented with diastolic blood pressure ≥120 mmHg, 27% of the patients were not referred to urgent care. These results indicate the importance of identifying patients with high diastolic blood pressure and referring them to appropriate treatment, according to their clinical priorities.